A complete cross section data set for electron scattering by pyridine: Modelling electron transport in the energy range 0–100 EV - Costa, Filipe (2020)
FIS2016-80440 PID2019-104727RB-C21 Project LINKA 20085 PD/00193/2012 PTDC/FISAQM/31281/2017 grant DP180101655